THU0006 Validation of Differential Methylation in Maternally Versus Paternally Transmitted Psoriatic Disease. (9th June 2015) - Pollock, R.A.; O'Rielly, D.D.; Dohey, A.; Codner, D.; Chandran, V.; Gladman, D.; Rahman, P.
Abstract : Background: Several studies have demonstrated excessive paternal transmission of psoriasis and psoriatic arthritis (PsA). This phenomenon is thought to be mediated by genomic imprinting. We previously compared whole blood methylation patterns among PsA patients from Newfoundland, Canada and identified 90 significant CpG sites that differentiate patients with paternally and maternally-transmitted disease. Objectives: To validate previously-identified CpG sites in an independent sample of PsA patients with paternally and maternally-transmitted disease from Toronto, Canada. Methods: All PsA patients included in the study satisfied the CASPAR criteria and had a parent with either psoriasis or PsA. Forty-six (46) PsA patients with paternally-transmitted disease were compared to 48 PsA patients with maternally-transmitted disease at 136 CpG sites on 10 different chromosomes. Percent methylation was measured at each CpG site by Sequenom EpiTyper technology, which involves bisulfite conversion followed by mass spectrometric analysis. Generated β values ranging from 0% (fully unmethylated) to 100% (fully methylated) were compared between groups using the nonparametric Mann-Whitney U test. Logistic regression models adjusting for age and sex were run to confirm the unadjusted results. Results: PsA patients with paternally-transmitted disease were 52% female, and at the time of sample collection had a mean (SD) age of 47.7 (12.6) years, psoriasis duration of 23.7 (13.3) years, PsA duration of 14.1 (9.7) years, PASI score of 5.3 (7.2) and tender joint count of 4.9 (7.8). Patients with maternally-transmitted disease were 53% female, and had a mean age of 50.3 (11.1) years, psoriasis duration of 23.1 (12.2) years, PsA duration of 14.9 (12.0) years, PASI score of 4.5 (5.3) and tender joint count of 6.8 (8.5). Three CpG sites were significantly differentially methylated in the Toronto patients with paternally and maternally-transmitted disease. The most significant site was located within an intron of the CROCC (rootelin) gene on 1p36.13 and was hypomethylated in paternally-transmitted disease (p=0.014). Two sites within the 5' UTR of the PACSIN1 gene on chromosome 6p21.3 were also significantly hypomethylated in paternally-transmitted disease (p=0.040 and p=0.047). After adjustment for age and sex, CpG methylation at CROCC remained significantly associated with paternally-transmitted disease (OR=0.77, 95% CI 0.60-0.99, p=0.04). Conclusions: CpG methylation at the CROCC locus on chromosome 1p36.13 differentiates PsA patients with paternally and maternally-transmitted disease. Although CROCC is not known to be imprinted in humans, these data suggest it may play some role in the excessive paternal transmission of psoriatic disease. Further validation of these results in somatic and germ line cells are necessary. Disclosure of Interest: None declared